PENINGKATAN SIFAT MEKANIK DAN TERMAL KAYU KELAPA SAWIT DENGAN TEKNIK KOMPREGNASI REAKTIF - ., Nurfajriani; Hutabarat, Wesly; ., Thamrin; Wirjosentono, Basuki; Gea, Saharman (JURNAL PENELITIAN SAINTIKA, 2014)
Characterization of Oil Palm Trunks (OPT) in height roddifferent OPT that compregnated with polystyrene resin modificationshave been done, polystyrene resins modified with acrylic acid and benzoyl peroxide incorporated into the OPT pore size 15x2x2 cm3 shaped beam that is placed in the compregnator has been modified with -5 atm pressure for 15 minutes. Based on the tensile tests conducted showed that the optimum mechanical properties of the OPT on the bottom of the stem height. with the addition of 20% resin. Similarly, the thermal properties OPT marked increases with increasing temperature degradation of OPT compregnated modified polystyrene resin at a concentration of 20%. From the above two tests showed that OPT improved quality of prior treatment compregnation, analysis of thermal degradation by using Thermogravimetry